Implementasi Kegiatan Ekstrakurikuler Ilmu Pengetahuan Alam Untuk Menanamkan Keterampilan Proses Sains di Sekolah Dasar - Nilla Azkiyah; Ika Candra Sayekti (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2023)
This research uses a descriptive qualitative research type. Data collection techniques are through observation, interviews, and documentation, while data analysis techniques are by collecting, reducing, presenting, and drawing conclusions. The results of this study: 1) extracurricular activity planning consists of determining material, methods and determining the schedule for extracurricular activities; 2) implementation of extracurricular activities through three stages, namely before the trial process, trial process and closing; 3) the assessment used in extracurricular activities is using group and individual assessments. The group assessment instrument is in the form of a non-test, while the aspects of group assessment are cooperation, cohesiveness, ability to express opinions. While individual assessment is in the form of LKPD answer tests 4) extracurricular activities have instilled science process skills which consist of aspects of observing, classifying, predicting, measuring, concluding and communicating; 5) constraints and solutions, namely students who do not bring tools and materials, this can be overcome by the teacher providing spare tools and materials, the next obstacle is a learning atmosphere that is not conducive, this can be overcome by the teacher providing stimulus with educational games that can increase interest student learning.